Zintl Salts Ba2P7X (X = Cl, Br, and I): Synthesis, Crystal, and Electronic Structures - Juli-Anna Dolyniuk; Kirill Kovnir (Crystals, 2013)
Two barium phosphide halides, Ba2P7Br and Ba2P7I, were synthesized and structurally characterized by single crystal X-ray diffraction. Both compounds crystallize in the monoclinic space group P21/m (No. 11) and are isostructural to Ba2P7Cl. The crystal structures of Ba2P7X (X = Cl, Br, I) feature the presence of heptaphosphanortricyclane P73− clusters along with halogen anions and barium cations. According to the Zintl concept, Ba2P7X compounds are electron-balanced semiconductors. Quantum-chemical calculations together with UV-Visible spectroscopy confirm the title compounds are wide bandgap semiconductors. The bonding in the P73− clusters was analyzed by means of electron localization function. The elemental compositions were confirmed using energy dispersive X-ray spectroscopy.